Beyond HR : the new science of human capital - Boudreau, John W. (Harvard Business School Pub., 2007)
In Beyond HR: The New Science of Human capital, John Boudreau and Peter Ramstad show you how to do this through a new decisions science-talentship. Through talentship, you move far beyond merely reactive mind-set of planning and budgeting for headcount and hiring and retaining talent.